Politik Dinasti dan Demokrasi di Aras Lokal - Nur Quma Laila; Hasse Jubba (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
This paper aims to describe the practice of dynastic politics that occurred in Banten and the strategies carried out by local elites in carrying out dynastic politics. In addition, this paper also aims to analyze how the impact caused by the existence of dynastic politics in Banten. This article is based on data obtained from literature studies where the literature used comes from journal articles, theses, and is accompanied by those that are relevant to the research topic. The collected data is then processed and analyzed using descriptive analysis techniques. The results of the study indicate that the practice of dynastic politics can be seen from the mapping of the power network followed by members of the Ratu Atut Chosiyah (RAC) family. The practice of dynastic politics was carried out with several strategies ranging from violent positioning, branding and segmenting to attract voters to placing relatives in many government and business positions. The dynastic politics not only causes the low political participation of the people but also shows the low quality of democracy in Banten. This paper concludes that democratization that gives power to the people is actually used by the oligarchic regime through the practice of dynastic politics for their own interest.